Dysregulation of Micro RNA-155 as a Biomarker in Iraqi Patients with Prostate Cancer - Al-saffar, Jinan MJ (Iraqi Journal of Science, 2021)
Chronic inflammation can induce proliferative events and posttranslational DNA modifications in prostate tissues through oxidative stress. The miR-155 expression is abnormally increased in tumors. Therefore, this study aims to explore the clinical significance of serum TNF-α and IL-1α as well as miR-155 expression in prostate cancer (PC) patients. A total of 50 blood samples from patients diagnosed with prostate cancer were collected from the Oncology Department, Baghdad Teaching Hospital, along with samples from 50 healthy volunteers. Serum TNF-α and IL-1α levels in Iraqi males with prostate cancer were estimated by using enzyme-linked immunosorbent assay (ELISA). The total RNA was extracted from all subjects and converted to cDNA using Stem-Loop technique and the expression was measured by real-time PCR (RT-PCR) using SYBR Green with specific primers. The results showed that serum TNF-α and IL-1α levels were significantly higher in the clinical stage of tumor node metastasis (TNM) as compared to those in the control (p<0.05). The miR- 155 level was significantly elevated in the patients compared with the control (p<0.05), being positively correlated with advanced stages. It is concluded that circulating miR-155 could act as a promising marker for the diagnosis and prognosis of PC.